Vivência de cuidadores familiares enlutados de crianças e adolescentes que morreram por câncer - Mutti, Cintia Flôres (2021)
Introduction: the child and adolescent's illness due to cancer can be painful for both them and their family caregivers. The losses faced throughout the process of disease progression until death are related to their physical, emotional, cognitive, social and spiritual dimension. Thus, the construction of senses and meanings attributed to these losses by family caregivers is considered essential in the process of grief elaboration. Objectives: to understand the experience of bereaved family caregivers in the illness and in the terminality of life of children and adolescents who died of cancer; to understand the experience of bereavement of family caregivers of children and adolescents who died of cancer. Method: This is a descriptive and exploratory research with qualitative data analysis, guided by the Psychosocial Transition Theory, ethological theory of attachment and the Dual Grief Process Model. The data were analyzed using Inductive Thematic Analysis (ITA). The place of selection of participants was a treatment center for children and adolescents with cancer of a university hospital in southern Brazil. Data collection occurred between the months of August 2018 and February 2020, through semi-structured interviews. Eight family caregivers of children/adolescents who died from cancer participated in this study. The ethical aspects were respected according to resolution 466/12, with approval from the Research Ethics Committee of the Federal University of Santa Maria. Results: The results pointed out that the understanding of the family caregivers' experiences made it possible to constitute distinct meanings attributed to the temporality of the events. The memories trigger several behaviors and feelings which are experienced daily. In the experience of family caregivers in the illness, it was verified the grief experienced by the memory of the trajectory of the bad moments, the physical and emotional suffering the child and adolescent had since the first symptoms manifested, the late diagnosis, the changes and restrictions due to the treatment causing a significant negative impact on the child and adolescent. In the experience of life terminality, it was noticed several events that were considered difficult for the family caregivers, because, for them, the child and adolescent had physical, psychosocial and emotional suffering, which occurred with greater intensity in the advanced disease and at the time of death. And in the experience of grief of family caregivers, it was understood that the reactions of grief caused by the loss of the child and adolescent are proportional to the affective bond that the caregivers had with them, and such a rupture left a deep and irreparable pain. Final considerations: it was concluded that the experience of bereaved family caregivers in the illness and in the terminality of life and in the mourning of children and adolescents who died from cancer is a complex phenomenon that involves suffering, memories, and loss. The need for the implementation of palliative care from the moment of the diagnosis of cancer, whether curable or not, to the necessary accompaniment in the bereavement process was verified.